Modal Sosial dalam Tata Kelola Wisata Pesisir: Studi di Pantai Delegan Kabupaten Gresik Pasca Pandemi - M. Husni Tamrin; Didin Muhafidin; Heru Nurasa; Entang Adhy Muhtar (Aliansi, 2022)
This study aims to examine the application of coastal area-based social capital in Gresik Regency. Social capital itself has a high role urgency in the context of development, including in the coastal area of Delegan Beach in Gresik Regency. The study of social capital has become a kind of standard with regard to making the community the main subject in the management of the coastal area of Delegan Beach. This study understands the extent of the application of community social capital and its implications in the coastal area of Gresik Regency through a qualitative approach and case studies on the aspect of using Delegan Beach for local life. The concept of social capital becomes the main reference in analyzing the findings in the field. The findings in this study are in the form of a well-organized pattern of community organization in the research area, a strong pattern of building trust and norms that apply between coastal communities, to the development of networks that are able to increase efficiency by facilitating coordinated actions in the dynamics of developing the coastal area of Delegan Beach towards coastal tourist destinations. The dominant groups that appear as subjects are the tourism-aware group (pokdarwis) around the coastal area of Delegan Beach and the Village-Owned Enterprises (BUMDes). However, there are still limited access (funding, licensing, coastal tourism development, and so on) in regional development which is the main problem that hinders the sustainability of local development in the community. The implication of this is that a touch from the government and related agencies such as the Department of Fisheries and Marine Affairs and the Tourism Office of the Gresik Regency Government is needed in an effort to continue development and support for the community around the coastal development of Delegan Beach in Gresik Regency. Penelitian ini bertujuan untuk mengkaji penerapan modal sosial berbasis kawasan pesisir di Kabupaten Gresik. Modal sosial sendiri memiliki urgensi peran yang tinggi pada konteks pembangunan, termasuk di kawasan pesisir Pantai Delegan di Kabupaten Gresik. Studi seputar modal sosial menjadi semacam pakem berkenaan dengan menjadikan masyarakat sebagai subyek utama dalam pengelolaan kawasan pesisir Pantai Delegan. Studi ini memahami sejauh mana penerapan modal sosial masyarakat beserta implikasinya di wilayah pesisir Kabupaten Gresik melalui pendekatan kualitatif dan studi kasus pada aspek pemanfaatan Pantai Delegan untuk kehidupan lokal. Konsepsi modal sosial menjadi referensi utama dalam menganalisis temuan di lapangan. Temuan dalam studi ini berupa pola pengorganisasian masyarakat di wilayah penelitian yang tergorganisir dengan baik, kuatnya pola pembangunan kepercayaan dan norma yang berlaku antar masyarakat pesisir, hingga pembangunan jejaring yang mampu meningkatkan efisiensi dengan adanya fasilitasi tindakan terkoordinasi dalam dinamika pembangunan kawasan pesisir Pantai Delegan menuju kawasan wisata bahari. Kelompok dominan yang tampil sebagai subjek yakni kelompok sadar wisata (pokdarwis) yang berada di sekitar kawasan pesisir Pantai Delegan dan Badan Usaha Milik Desa (BUMDes). Namun demikian, masih adanya keterbatasan akses (pendanaan, perizinan, pembembangan wisata pesisir, dan sebagainya) dalam pembangunan kawasan menjadi permasalahan utama yang menghambat keberlanjutan pembangunan lokal di masyarakat. Implikasi dari adanya hal tersebut, maka sangat dibutuhkan sentuhan dari pemerintah dan dinas terkait seperti Dinas Perikanan dan Kelautan serta Dinas Pariwisata Pemerintah Kabupaten Gresik dalam upaya pengembangan lanjutan dan dukungan bagi masyarakat seputar pembangunan pesisir Pantai Delegan di Kabupaten Gresik.